2017
DOI: 10.1111/jpn.12653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation–anion balance in feed on urine pH in rabbits in comparison with other species

Abstract: In the present investigation, the impact of diet composition on urine pH in rabbits was compared with previous studies on rabbits, cats, dogs, pigs and horses. A total of 13 dwarf rabbits were fed six different diets with a cation-anion balance (CAB) between -39 and +320 mmol/kg dry matter (DM) using ammonium chloride (NH Cl) as an acidifier. CAB was calculated as follows: CAB (mmol/kg DM) = 49.9*Ca + 82.3*Mg +43.5*Na + 25.6*K - 59*P - 62.4*S - 28.2*Cl; minerals in g/kg DM. Urine, faeces and blood were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…There could be strain differences in the absorption of dietary cations and anions from the gastrointestinal tract. The activity of carboanhydrase, the enzyme for renal H + excretion, plays a role in the potential change in urinary pH [4]. The possibility of strain differences in expression of this enzyme should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There could be strain differences in the absorption of dietary cations and anions from the gastrointestinal tract. The activity of carboanhydrase, the enzyme for renal H + excretion, plays a role in the potential change in urinary pH [4]. The possibility of strain differences in expression of this enzyme should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The diets were analyzed for minerals (Table 1) and the DCAB was calculated from these values using the following equation [1,3,4,6] Once a week, during the cage changing, spontaneous urination is known to occur [27,28]. This behavior was used to collect as much urine as possible per mouse without stressful or invasive manipulation.…”
Section: Feeding Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial bene t of feeding a low-DCAD diet was reported by Block [2], who observed that treatment with − 172.3 (mmol/kg DM) DCAD could prevent hypocalcemia compared to a control DCAD of + 448.6 (mmol/kg DM). The DCAD level has been an important parameter in the process of formulating diets in recent years [3][4][5][6][7]. Studies have shown that diets with a lower DCAD could enhance the health and extend the economic life of transition mammary animals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%